Cancer risk of heterozygotes with the NBN founder mutation - Seemanová, Eva; Jarolím, Petr; Seeman, Pavel; Varon, Raymonda; Digweed, Martin; Swift, Michael; Sperling, Karl (Journal of the National Cancer Institute, 2007)
BACKGROUND: The autosomal recessive chromosomal instability disorder Nijmegen breakage syndrome (NBS) is associated with increased risk of lymphoid malignancies and other cancers. Cells from NBS patients contain many double-stranded DNA breaks. More than 90% of NBS patients are homozygous for a founder mutation, 657del5, in the NBN gene. We investigated the 657del5 carrier status of cancer patients among blood relatives (i.e., first-, through fourth-degree relatives) of NBS patients in the Czech Republic and Slovakia to test the hypothesis that NBN heterozygotes have an increased cancer risk. METHODS: Medical information was compiled from 344 blood relatives of NBS patients in 24 different NBS families from January 1, 1998, through December 31, 2003. The 657del5 carrier status of subjects was unknown at the time of their recruitment but was later determined from blood samples collected at the time of the interview. Medical records and death certificates were used to confirm a diagnosis of cancer. For the relatives with cancer who are not obligate heterozygotes (such as parents and two grandparents in consanguineous families), the observed and expected number of mutation carriers were compared by use of the index-test method, which estimated the risk of cancer associated with carrying the mutation. All P values were two-sided. RESULTS: Thirteen of the 344 blood relatives had confirmed cases of any type of cancer; 11 of these 13 cancer patients carried the NBN 657del5 mutation, compared with 6.0 expected (P = .005). Among the 56 grandparents with complete data from 14 NBS families, 10 of the 28 carriers of 657del5, but only one of the 28 noncarriers, developed cancer (odds ratio = 10.7, 95% CI = 1.4 to 81.5; P<.004). CONCLUSIONS: The NBN 657del5 mutation appears to be associated with an elevated risk of cancer in heterozygotes.
Keywords: Founder Effect; zlomy chromozomů; zárodečné mutace; dospělí; financování organizované; Nuclear Proteins; heterozygot; Nijmegen Breakage Syndrome; nádory prsu; kolorektální nádory; odds ratio; Research Design; Female; Germ-Line Mutation; Adult; ženské pohlaví; delece genu; mutační analýza DNA; Neoplasms; Colorectal Neoplasms; Slovakia; lidé; Heterozygote; Genital Neoplasms, Female; Breast Neoplasms; DNA Mutational Analysis; Stomach Neoplasms; genetická predispozice k nemoci; Aged, 80 and over; Risk Assessment; Genetic Predisposition to Disease; Financing, Organized; Risk Factors; Genetic Carrier Screening; Cell Cycle Proteins; Gene Deletion; Male; Aged; efekt zakladatele; Czech Republic; Chromosome Breakage; detekce genetických nosičů; Česká republika; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; proteiny buněčného cyklu; nádory ženských pohlavních orgánů; Retrospective Studies; Middle Aged; Odds Ratio; Humans